Construction Planning, Equipment, and Methods - Peurifoy, Robert L.; Schexnayder, Clifford J.; Schmitt, Robert L.; Shapira, Aviad; Cohen, Aaron (McGraw Hill, 2024)
Construction planning techniques, technology, and applications--fully updated for the latest advances This thoroughly revised guide covers the fundamentals of construction equipment, machinery utilization, and production estimating. You will learn about construction economics, earthwork, and soil and rock properties. Rock blasting and drilling, pile driving, water pumping, and concrete and asphalt construction procedures are clearly explained. The book also contains technical depth for calculating machine production capability. Construction Planning, Equipment, and Methods, Tenth Edition lays out the latest technologies and shows how to apply those technologies to real-world construction projects--all with an emphasis on cutting-edge machine capabilities. Examples and illustrations showcase the latest equipment models, while chapter summaries and homework problems help reinforce salient points. Presented in a logical and concise format, this up-to-date edition features new chapters on trenches, trenchless technology, and virtual design. Provides a concise, student-friendly introduction to construction methods and planning Contains new problems, Excel answer sheets, and a refreshed solutions manual Written by team of construction management experts and experienced educators.